Pengaruh Kompensasi Finansial dan Non Finansial Terhadap Motivasi Kerja Karyawan Universitas Brawijaya Hotel Kota Malang - Wisudawan, Alif Furqoni Aulia; Troena, Eka Afnan (Jurnal Ilmiah Mahasiswa FEB, 2012)
Abstract: This research basically aimed to determine the effect of financial and non-financial compensation for employee motivation. The site chosen for this study is the UB Hotel Malang. This research was conducted to 62 respondents using a quantitative approach. Thus, the data analysis is the statistical analysis in the form of multiple linear regression. The results showed that these two independent variables (financial and non-financial compensation) simultaneously significant effect on employee motivation by test F = 6148 (Sig. 004). While the effect of partial, non-financial compensation variables significantly influence employee motivation with sig. 025 (t = 2,301). From the second independent variable was also found that non-financial compensation is the most variable in the variable has an impact on employee motivation. Â  Keywords: compensation, financial compensation, non-financial compensation, employee motivation, UB Hotel Malang